Islam & Europe : Crises are Challenges - Aboutaleb, Ahmed; Carlier, Jean-Yves; Foblets, Marie-Claire, 1959- (Book collections on Project MUSE., 2010)
Within the framework of the Forum A. & A Leysen, several experts from in and outside the Muslim world contributed to this book. In Islam and Europe: Crises Are Challenges they discuss how dialogues between Islam and the West, with a focus on Europe, can be achieved. The various authors (legal scholars, political theorists, social scientists, and psychologists) explore in these collected essays such interrelated questions as: How much diversity is permissible within a liberal pluralistic democratic society? How strong are the implications of citizenship? What are equitable accommodations of cont.